2007
DOI: 10.2215/cjn.00860207
|View full text |Cite
|
Sign up to set email alerts
|

Current Management of Vascular Access

Abstract: Optimizing vascular access outcomes remains an ongoing challenge for clinical nephrologists. All other things being equal, fistulas are preferred over grafts, and grafts are preferred over catheters. Mature fistulas have better longevity and require fewer interventions, as compared with mature grafts. The major hurdle to increasing fistula use is the high rate of failure to mature of newly created fistulas. There is a desperate need for enhanced understanding of the mechanisms of failure to mature and the opti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
232
1
6

Year Published

2008
2008
2016
2016

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 254 publications
(242 citation statements)
references
References 179 publications
3
232
1
6
Order By: Relevance
“…Once this occurs, continued hemodialysis requires a choice between placing an arteriovenous graft in the thigh or long-term dependence on tunneled hemodialysis catheters (1). All grafts are prone to recurrent stenosis and thrombosis, which can lead to permanent access failure (2), but there are few publications on the outcomes and complication of thigh grafts. Most published studies reported the outcomes of relatively few thigh grafts, with inconsistent definitions of graft outcomes (3)(4)(5)(6)(7)(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…Once this occurs, continued hemodialysis requires a choice between placing an arteriovenous graft in the thigh or long-term dependence on tunneled hemodialysis catheters (1). All grafts are prone to recurrent stenosis and thrombosis, which can lead to permanent access failure (2), but there are few publications on the outcomes and complication of thigh grafts. Most published studies reported the outcomes of relatively few thigh grafts, with inconsistent definitions of graft outcomes (3)(4)(5)(6)(7)(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…Anticoagulant solutions are instilled into both catheter lumens after each dialysis session in an effort to prevent interdialytic catheter thrombosis (1). Heparin is the predominant anticoagulant lock solution used in U.S. hemodialysis units.…”
mentioning
confidence: 99%
“…Mortality rate has been shown to be significantly higher in those who dialyse first by means of tunnelled catheters, and at the same time, they are at increased risk of failure of subsequent AVF [7,9,10]. Arteriovenous grafts tend to have better primary patency rates compared to AVF [6,11,12], however AVFs last longer, and with the exception of those fistulas which fail to mature primarily, the cumulative patency (from formation to permanent failure) is superior to grafts; moreover, AVFs-once they fully mature-are less likely to require secondary procedures for vascular access salvage to maintain patency, including angioplasty, stenting or thrombectomy [6,[13][14][15][16]. The 2006 updated NKF-KDOQI Guidelines recommend AVF prevalence of 65% for patients undergoing HD [17].…”
Section: Introductionmentioning
confidence: 99%